2022
DOI: 10.3390/ijerph19063729
|View full text |Cite
|
Sign up to set email alerts
|

Designing of a Recombinant Multi-Epitopes Based Vaccine against Enterococcus mundtii Using Bioinformatics and Immunoinformatics Approaches

Abstract: Enterococcus species are an emerging group of bacterial pathogens that have a significant role in hospital-associated infections and are associated with higher mortality and morbidity rates. Among these pathogens, Enterococcus mundtii is one of the causative agents of multiple hospital associated infections. Currently, no commercially available licensed vaccine is present, and multi-drug resistant strains of the pathogen are prominent. Due to several limitations of experimental vaccinology, computational vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Targets were identified that could be part of the pathogen core proteome and nonredundant. Extracellular proteins being surface proteins were used and subjected to different vaccine filters to obtain the potential targets [ 76 ]. Proteins were examined for the presence of transmembrane helices, allergenicity, antigenicity, and physicochemical properties to screen experimental, feasible, and effective vaccine targets [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targets were identified that could be part of the pathogen core proteome and nonredundant. Extracellular proteins being surface proteins were used and subjected to different vaccine filters to obtain the potential targets [ 76 ]. Proteins were examined for the presence of transmembrane helices, allergenicity, antigenicity, and physicochemical properties to screen experimental, feasible, and effective vaccine targets [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epitope mapping of the selected core proteins was performed via immunoinformatic tools/server, and ten led to epitope prioritization [ 76 ]. B-cell-derived T-cell epitopes were predicted and selected on the basis of their antigenicity, nonallergenicity, solubility, and nontoxicity potential to be a part of the MEPTWV.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, several filters were applied on the selected outer membrane, extracellular and periplasmic proteins to perform selection of potential vaccine targets. Proteins that play a significant role in pathogenesis are prime targets for vaccine design ( Ahmad et al, 2019 ; Alharbi et al, 2022a ). A BLASTp search was conducted against the core virulent factor database (VFDB) ( Liu et al, 2019 ) using output proteins from the subcellular localization step, and those with sequence identities of ≥ 30% and bit scores ≥ 100 were selected ( Qamar et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The linkers used prevent epitopes from folding over one another and keep the epitopes separated so they can be easily presented to the host immune system [35]. After the construction of the vaccine construct, the physicochemical properties were analyzed for the designed vaccine construct using Protparam [41].…”
Section: Multi-epitope-based Vaccine Designing and Processing Phasementioning
confidence: 99%